Life Design Counseling: Theory, Methodology, Challenges, and Future Trends - Wen, Ya; Li, Kai; Chen, Huaruo; Liu, Fei (Frontiers in Psychology, 2022)
With the rapid development of society and the dramatic change of environment, previous career counseling focusing on personal choice has been difficult to meet individuals’ needs. It is very meaningful and valuable to introduce the ideology of Life Design Counseling (LDC). In this mini review, we introduce and analyze the theory and methodology of LDC. This review puts forward challenges in the field of LDC, including the lack of attention to clients from multiple backgrounds and professional counselors, the lack of diversified methods in the intervention process, and the lack of diversified research. The theoretical research, practical research, and the integration of theory and practice of LDC still need to be further concerned by researchers.